Additional file 2 of Discovery of an autophagy inducer J3 to lower mutant huntingtin and alleviate Huntington’s disease-related phenotype - Jiahui Long; Xia Luo; Dongmei Fang; Haikun Song; Weibin Fang; Hao Shan; Peiqing Liu; Boxun Lu; Xiao-Ming Yin; Liang Hong; Min Li (figshare, 2022)
Additional file 2: Figure S2. WT-HeLa cells were incubated with 20 μM of J3 with or without 2 mM of NAC, 1 μM of compound C, 10 μM of U0126, 10 μM of BAPTA for 6 h, respectively. The protein level of LC3-II was detected by western blot and quantified.
Keywords: Biochemistry; Cell Biology; Genetics; Molecular Biology; Neuroscience; Physiology; Chemical Sciences not elsewhere classified